Commonity Development Through Comparison of Learning Methods and OBE-Based Civil Engineering Curriculum at Putra Malaysia University - Akbardin, Juang; Permana, Asep Yudi; Mohamad, Dadang; Samsudin, Achmad (Pusat Pengembangan dan Kajian Sarana dan Prasarana Pendidikan (P2K Sarprasdik), 2024)
Improving the OBE-based curriculum requires strengthening based on comparison and experience in its implementation. The method of implementing service used is active participation based on a comparison of the learning methods used and the designed curriculum. The service results obtained are a draft design for developing a comprehensive Civil Engineering OBE-based curriculum in terms of the input and output produced. Forms of sustainable institutional partnership cooperation are formulated in stages and efforts are made to implement scientific development policies. The comparison of the UPI-UPM Civil Engineering curriculum was carried out through FGD (Forum Group Discussion) using an interactive method. Expertise groups provide opinions and arguments related to the application of courses and student loads in carrying out learning in Civil Engineering. Determination of the curriculum framework and implementation of OBE is carried out in a measurable manner by applying the Washington Accord instruments as a reference for administering the Civil Engineering Curriculum. The comparison of the Civil Engineering OBE curriculum m-UPI – UPM produces a collaborative approach to implementing academic activities that encourages further development at the next stage of implementing academic activities. The development of the OBE curriculum based on the Washington Accord standards for UPI and UPM Civil Engineering requires a more technical, collaborative implementation. The UPI-UPM Civil Engineering academic collaboration agreement will be followed up with comprehensive academic collaboration with more intense academic communication.